2018
DOI: 10.1101/322560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engagement of pulvino-cortical feedforward and feedback pathways in cognitive computations

Abstract: Computational modeling of brain mechanisms of cognition has been largely focused on the cortex, but recent experiments have shown that higher-order nuclei of the thalamus, in particular the pulvinar, participate in major cognitive functions and are implicated in psychiatric disorders. Here we show that a pulvino-cortical circuit model, composed of two cortical areas and the pulvinar, captures a range of physiological and behavioral observations related to the macaque pulvinar. Effective connections between the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 122 publications
(272 reference statements)
5
56
0
Order By: Relevance
“…The "cognitive thalamus" hypothesis postulates that the region is a key modulating hub for corticocortical interactions. [118][119][120] According to the hypothesis, high-order thalamic nuclei (ie, associative and posterior nuclei) exhibit critical functional and structural connections with the DMN, 71 thereby affecting network activity and, ultimately, cognition. The activity of high-order thalamic nuclei is under the control of cholinergic neurons that project from the PPN to the TRN.…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%
“…The "cognitive thalamus" hypothesis postulates that the region is a key modulating hub for corticocortical interactions. [118][119][120] According to the hypothesis, high-order thalamic nuclei (ie, associative and posterior nuclei) exhibit critical functional and structural connections with the DMN, 71 thereby affecting network activity and, ultimately, cognition. The activity of high-order thalamic nuclei is under the control of cholinergic neurons that project from the PPN to the TRN.…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%
“…The impact of cerebellar activation on individual LFP signals in wS1 or wM1 as well as that on the coherence between these signals could be well replicated by our modeling work. We built our computational model on cerebellar modulation of cortical interactions by expanding our existing model on cortico-cortical and thalamo-cortical interactions (Mejias et al, 2016;Jaramillo et al, 2019), The model, the connectivity of which is constrained by realistic anatomical routes, suggests that Purkinje cell activity triggers a disinhibitory effect via the zona incerta, which in turn mediates both the suppression of gamma coherence and the enhancement of theta coherence between S1 and M1. In agreement with the experimental data, the model revealed that sensory-induced gamma band coherence involved mainly signals originating from S1, but with a substantial contribution of M1.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of coherence among different cortical regions implicates reciprocal connections between neurons distributed among different layers within the cerebral cortex (Cardin et al, 2009;Buzsáki and Wang, 2012;Jensen et al, 2014;Mejias et al, 2016;Veit et al, 2017) as well as inputs from subcortical structures like the thalamus (Pedroarena and Llinás, 1997;Saalmann et al, 2012;Song and Francis, 2015;Jaramillo et al, 2019) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Computationally, higher order thalamic nuclei (which include those in the midline 55,56 ) have been proposed to gate communication between neocortical areas. This 'gate' may be implemented through direct control of cortical synchronization and effective connectivity [57][58][59] , and through the regulation of the signal-to-noise ratio in resting states 28 . The broad decrease in thalamic activity at the time of potential memory reactivation in CA1, could facilitate effective information transfer between hippocampus and neocortex by reducing interference from the main input (thalamic) to neocortical areas.…”
Section: Thalamic Inhibition During Hippocampal Swrsmentioning
confidence: 99%